Environmental temperature and light intensity recorded at Tule Red Tidal Restoration Site from October 2020 through December 2021 - Richelle L Tanner; Lorna E Haworth; Sarah Nancollas; Susie N Landa; Anne E Todgham (PANGAEA, 2024)
Eight HOBO Pendant Temperature/Light 64K Data Loggers (Onset Computers) were installed among native and Phragmites canopies (n = 4 each) in the Tule Red Tidal Restoration Project within Suisun Marsh (38.118588, -121.980767). Four of these loggers were placed at the edge of a secondary tidal channel in the vegetation stand and four were placed 20 m perpendicular to the tidal channel onto the marsh plain. The loggers recorded temperature (°C) and light intensity (lumens/ft^2, or lux) continuously every 15 minutes from October 2020 through December 2021. The data used to create the laboratory conditions were isolated from the first 10 days of May 2021. The most extreme representations of each habitat (native and Phragmites) were used as the environmental conditions for each laboratory treatment: 12.7-35.7 °C and 11,229 lumens for the native habitat and 13.6-24.3 °C and 3,341 lumens for the Phragmites habitat, both on a semidiurnal tidal cycle.
In: Tanner, RL et al. (2024): Amphipod protein, glycogen, and glucose content under simulated invasion stress in wetlands [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973173